2014
DOI: 10.2135/cropsci2013.09.0649
|View full text |Cite
|
Sign up to set email alerts
|

Biotypic Variation among Soybean Aphid Isolates from Four Provinces in China

Abstract: The soybean aphid [Aphis glycines Matsumura (Hemiptera: Aphididae)] is an important pest insect of soybean [Glycine max (L.) Merr.] in China and North America. Identification of soybean aphid biotypes would facilitate more effective pest management. Although four soybean aphid biotypes have been discovered in North America to date, biotype determination has not been conducted in China. In this study, we analyzed the biotypes of soybean aphids collected from four different soybean‐growing areas in China in 2011… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…The aphid populations from Wisconsin, the state where the SBA was first reported in the U.S. in 2000, showed higher virulence variability [23]. Additionally, Zhong, et al [28] reported at least four biotypes of SBA in China. These biotypes were named China Biotype 1 (virulence on host plants with Rag5 or Rag6 ), China Biotype 2 (virulence on host plants with Rag1 , Rag3 , or Rag5 ), China Biotype 3 (virulence on host plants with Rag1 , Rag3 , or Rag6 ), and China Biotype 4 (virulence on host plants with Rag1 , Rag2 , Rag3 , or Rag5 genes) [28].…”
Section: Soybean Aphidmentioning
confidence: 99%
“…The aphid populations from Wisconsin, the state where the SBA was first reported in the U.S. in 2000, showed higher virulence variability [23]. Additionally, Zhong, et al [28] reported at least four biotypes of SBA in China. These biotypes were named China Biotype 1 (virulence on host plants with Rag5 or Rag6 ), China Biotype 2 (virulence on host plants with Rag1 , Rag3 , or Rag5 ), China Biotype 3 (virulence on host plants with Rag1 , Rag3 , or Rag6 ), and China Biotype 4 (virulence on host plants with Rag1 , Rag2 , Rag3 , or Rag5 genes) [28].…”
Section: Soybean Aphidmentioning
confidence: 99%